The Role of Pencak Silat in Forming Youth Character - Utomo, Mulyo; Wargo, Wargo; Musthofa, M. Arif (Zabags International Journal of Education, 2023)
Damage to the morale of Indonesian youth due to the swift flow of foreign culture. Globalization results in the loss of boundaries between nations and facilitates the entry of culture, information, and negative influences from other countries. The character of youth, which should be based on Pancasila and the constitution as the identity of the Indonesian nation, has shifted to become a hedonic, capitalist, and individualist character. Pencak silat, as the work of the Indonesian nation, is able to become a vehicle for the formation of the proper character of the nation's youth. Pencak silat coaching with well-utilized physical, spiritual, and emotional elements can produce young individuals who have noble character. This research is qualitative research, with an inductive analysis methodology that takes place during the research process. The key informants consisted of students, trainers, and alumni of the STIE Syari’ah Al-Mujjaddid Commissariat PSHT. The data was obtained during the routine practice of pencak silat. Data collection techniques using interviews, observation, documentation, and internet content. The results of the study show that the formation of youth character can be carried out through training in pencak silat at the STIE Syari’ah Al-Mujaddid PSHT Commissariat, which is based on five basic principles, namely: brotherhood, sports, martial arts, fine arts, and spirituality. Meanwhile, the youth characters that can be formed are polite, disciplined, brave, simple, love for the motherland, devoted to parents, country, and religion. The concept of forming youth character through pencak silat is in line with PSHT's goal of participating in forming human beings who have noble morals, understand right and wrong, and have faith in God Almighty.